Seeking a Sanctuary, Second Edition : Seventh-day Adventism and the American Dream - Bull, Malcolm (Book collections on Project MUSE., 2007)
The completely revised second edition further explores one of the most successful of America's indigenous religious groups. Despite this, the Adventist church has remained largely invisible. Seeking a Sanctuary casts light on this marginal religion through its socio-historical context and discusses several Adventist figures that shaped the perception of this Christian sect.